Mapping of Food Crop Commodity Production Areas in Indonesia Using The Average Linkage Method - Hery Priandoko; Alva Hendi Muhammad; Anggit Dwi Hartanto (Fakultas Teknik Universitas Lambung Mangkurat, 2024)
Indonesia consists of several regions that have the potential to meet food needs. One of the main sectors that meet food needs is the agricultural sector. The agricultural sector is a sector that needs significant attention from the central and regional governments in meeting national food needs. Food needs are currently often scarce so people find it difficult to obtain these food needs. The problem of dependence on food needs can endanger the availability of the country's food supply. Importing food crop commodities is one solution to maintaining food availability in Indonesia. Imports of food crop commodities carried out by Indonesia show that the amount of food commodity availability cannot meet national food needs. In Indonesia, some regions have food crop commodity production so that they can help in the availability of these food needs. From the existing problems, researchers tried to conduct research by mapping the regions or areas in Indonesia to find out which regions have food crop commodity production. In this study, the mapping that will be used is using the hierarchical cluster method. The hierarchical cluster method that will be used is the agglomerative hierarchical cluster method with the average linkage method. The results of this study will be formed into 3 clusters with the following details: high cluster, medium cluster, and low cluster. The highest cluster obtained 2 members, namely the Provinces of East Java and Central Java. The Medium Cluster obtained 1 member, namely the Province of West Java. The Low Cluster obtained 31 members, namely the Provinces of Aceh, North Sumatra, West Sumatra, Riau, Jambi, South Sumatra, Bengkulu, Lampung, Bangka Belitung Islands, Riau Islands, DKI Jakarta, DI. Yogyakarta, Banten, Bali, West Nusa Tenggara, East Nusa Tenggara, West Kalimantan, Central Kalimantan, South Kalimantan, East Kalimantan, North Kalimantan, North Sulawesi, Central Sulawesi, South Sulawesi, Southeast Sulawesi, Gorontalo, West Sulawesi, Maluku, North Maluku, West Papua, and Papua.